Nationwide surveillance of pESI-positive Salmonella Infantis ST32 in South Korea: Endemic establishment of a dominant lineage across the broiler production chain, 2020–2023 - Hee-Seung Kang; Md.Sekendar Ali; Bo-Youn Moon; Min Young Kim; Yu-Jeong Hwang; Ji-In Kim; Seung-Chun Park; Jae-Myung Kim; Suk-Kyung Lim (Food Microbiology, 2027)

Comparative genomics and phenotypes of Listeria monocytogenes isolated from enoki mushrooms in South Korea and China - Wen Si Hu; So Hyeon An; Dong Woo Kim; Hyeong Uk Im; Seung Hun Lee; Yu Bao Li; Zi Xuan Liu; Zhi Wei Wang; A Ram Lee; Ui In Kim; Hyeon Ji Je; Yeon Ju Seo; et al. (Food Microbiology, 2026)

Accelerated chondrogenic differentiation of stem cells by SOX9 mRNA/dexamethasone-co-loaded lipid nanoparticle for efficient cartilage repair - Ji Sun Park; Hayoung Jeon; Yeeun Lee; Seong Gi Lim; Seo Young Cheon; In-Beom Kim; Hongsoo Choi; Heebeom Koo (Chemical Engineering Journal, 2026)

Aspect ratio control of polymer microparticles in shear-yielding emulsion systems via rheology-mediated shape arrest - Ji Hee Lee; Seung Min Baek; Siwoo Kim; In Jun Lee; Jaejun Lee; Sookyoung Jeon; Sang Yup Kim (Chemical Engineering Journal, 2026)

Development of Korea Air quality observation-based Box model (KAB) - Haeju Lee; Na-Hyeon Kim; Seonghui Lim; Minjoong J. Kim; Minseung Yeo; Min Young Kim; Taehyeon Kim; Ho-Jin Lim; Chang Hoon Jung; Ji Yi Lee; In Ho Song; Gookyoung Heo; et al. (Atmospheric Environment, 2026)

Machine learning-based spatiotemporal modeling and health risk assessment of PAHs and metals in an industrial city - Jeong-Tae Ju; Sang-Jin Lee; In-Gyu Cho; Ji Yoon Choi; Taekyu Kim; Sung-Deuk Choi (Atmospheric Environment, 2026)

Quadruple co-infection with Mycobacterium tuberculosis complex and M. kansasii in a chronically immunosuppressed cat - Sungyoung Choi; Soo-Nyun Choi; Tak Gyeom Lee; Sungweon Ryoo; Ji-Hoon Kwak; Kun-Woo Kim; Tae In Park; Woo-Jin Song; Eun-Joo Lee; Kyu-Shik Jeong (Veterinary Research Communications, 2026)

Allergenicity of edible insect proteins: Cross-reactivity, processing effects, and food safety considerations - Jae Hoon Lee; Ji Yoon Cha; Seonmin Lee; Yea-Ji Kim; Jeong-Heon Kim; Dong Hyun Keum; Hae In Yong; Min Hyeock Lee; Yun-Sang Choi (Food Chemistry, 2026)

Microphysiological system-based respiratory toxicity assessment: recent advances and regulatory perspectives - In Jae Bang; Min-Seok Kim; Yubin Han; Ga Eun Kim; Jung Eun Lim; Ji Yeong Park; Jin Yoo; Young Seo Jang; Beomhee Lee; Minjin Kwak; Soojin Park; Wonjun Jang; et al. (Toxicological Research, 2026)

Occupational risk assessment of p-tert-butylphenol: toxicity reference values and worker exposure evaluation - In Jae Bang; Ji Hyun Yu; Jung Eun Lim; Yubin Han; Yerim Koo; Damee Eun; Daeyeop Lee; Ig-Chun Eom; Ha Ryong Kim (Toxicological Research, 2026)

Application of Fibronectin-Coated Microparticles for Isolation of Human iPSC-Derived MSCs - Jae Hyeok Jang; In Sun Hwang; Ji Seob Kim; Sunjun Lee; Min Hee Moon; Bowon Kim; Seo Jeong Kim; Jongho Choi; Young Her; Soo-Hong Lee; Byung-Hyun Cha (Tissue Engineering and Regenerative Medicine, 2026)
BACKGROUND : Bone marrow–derived MSCs (BMMSCs) are limited by availability, donor variability, and age-related decline, highlighting the need for alternative MSC sources. Induced pluripotent stem cells (iPSCs) offer a scalable solution. This study introduces a novel three-dimensional culture platform based on fibronectin (FN)-coated microparticles to efficiently derive and expand human iPSC-derived MSCs (iMSCs). METHODS : The system utilizes FN-coated non-porous (CytoDex) and porous (CytoPore) microparticles. FN coating efficacy on microparticle was confirmed using Rhodamine-labeled FN and confocal microscope. Base on various molecular cell biological experiment, the utilization of FN-coated CytoDex and CytoPore leverages an expanded surface area to improve iMSCs isolation. The characteristics and cell behaviors of iMSCs generated from FN-coated CytoDex and CytoPore was evaluated by immunophenotype analysis, cell proliferation, and senescence related assays. In vivo tissue regeneration was evaluated by microcomputed tomography and histopathological analyses. RESULTS : The porous microparticle CytoPore significantly enhanced FN coating efficiency, cell attachment, and proliferation compared to CytoDex. FN-coated CytoPore enabled the selective isolation of a high-purity MSC population from spontaneously differentiated iPSCs (SD-iPSCs) by day 7, confirmed by distinct morphology and mesodermal marker expression. The resulting iMSCs exhibited immunophenotypic characteristics comparable to adult MSCs, along with superior proliferative capacity, extended telomere length, and minimal senescence over 10 passages, in contrast to BMMSCs. Furthermore, iMSCs demonstrated effective in vivo tissue regeneration in an osteochondral defect model. CONCLUSION : This novel FN-coated microparticle-based 3D culture platform enables efficient, large-scale production of high-quality iMSCs and holds strong potential for clinical applications in stem cell therapeutics and regenerative medicine.

Reassembled yeast vacuoles preserve endothelial viability and barrier integrity in an in vitro blood–brain barrier model - Yoon-Young Hwang; Cho-Im Oh; Jin-Pyo Lee; Su-Min Lee; Dae-Young Park; In-Hwan Oh; Tae-rim Kim; Ok Chan Jeong; Ji-Young Ahn; Yang-Hoon Kim; Jiho Min (Molecular & Cellular Toxicology, 2026)

Interaction of SFPQ with S100A8 and S100A9 in EoL-1 and EoL-1-IR cells - Jae Ha Baek; Geunyeong Kim; Yujin Hong; Min Hwa Hong; Ji-Sook Lee; Ik-Chan Song; Soo-Jung Gong; In Sik Kim (Molecular & Cellular Toxicology, 2026)

Bee pollination enhances fruit development and delays ripening by modulating the transition of ethylene biosynthesis and receptor dynamics in tomato (Solanum lycopersicum L.) - Ji Yeong Ham; Yong-Tae Kim; Jong Hwa Shin; Keono Kim; Jeehye Sung; Chuleui Jung; Hataitip Nimitkeatkai; Bongsu Choi; Byung-Chun In (Horticulture, Environment, and Biotechnology, 2026)

Genome-scale model-guided microbial engineering for valorization of agricultural waste biomass to poly(3-hydroxybutyrate) - Chae-Rim Jeong; Jaeseong Hwang; Young-Kwon Park; Jae Yong Ryu; Yong Hee Han; Ji Young Jeong; In Min Hwang; Ryeongeun Kim; Jung Eun Yang (Bioresource Technology, 2026)

AI-driven non-intrusive occupant monitoring for occupant-centric control: A multi-domain review of thermal, air, and visual environments - Ji Young Yun; Jin Woo Moon; Kang Woo Bae; Jun Kyu Kim; Hae Won Lee; Hye In Kim; Jae Ho Sung; Michael Kim (Building and Environment, 2026)

Marine algae growth and carbon capture augmentation by antioxidant nanozymes - Supreetha Sivaraj; Hye-In Kim; Su-Ji Jeon; Arnav Deshpande; Conor P. Murphy; Sandeep Sharma; Robert E. Jinkerson; Lieve M.L. Laurens; Juan Pablo Giraldo (Algal Research, 2026)

Characterisation and mechanism of action of the antimicrobial activity of hetero-exopolysaccharide from Lentilactobacillus buchneri KU200793 against Staphylococcus aureus and Listeria monocytogenes - Manoj Kumar Yadav; Ji Hoon Song; Robie Vasquez; Jae Seung Lee; Young-Seo Park; Hyun-Dong Paik; In Ho Kim; Dae-Kyung Kang (Archives of Microbiology, 2026)

Lithology and redox–hydration state of the mantle source of the late Cenozoic Baekdusan (Changbaishan) basalts, North China Craton - Na Eun Yeo; Sung Hi Choi; Yongjae Yu; Ji-In Kim (Journal of Asian Earth Sciences, 2026)

Near-infrared light–responsive implantable module integrated into glaucoma drainage device for controlled antifibrotic drug therapy - Chang Hee Min; Young In Shin; Han Bi Ji; Soo Bin Yoon; Yeonseo Kim; Cho Rim Kim; Jae Hoon Han; Min Ji Kim; Myung Ju Kim; Eun Jung Kwon; Young Kook Kim; Ki Ho Park; et al. (Chemical Engineering Journal, 2026)

ROMP-derived polymer binders with stepwise and facile multifunctionalization for high-performance silicon anode Li-ion batteries - Cheol Shin; Ji Young Kim; Gyuri Kim; Hansu Kim; In Hwan Jung (Chemical Engineering Journal, 2026)

A Fucose-containing Hetero-exopolysaccharide From Levilactobacillus brevis B151 Exhibits Potent Antimicrobial, Antibiofilm, and Antioxidant Activities - Manoj Kumar Yadav; Remilyn M. Mendoza; Ji Hoon Song; Robie Vasquez; Jae Seung Lee; Yeong-Seo Park; Hyun-Dong Paik; In Ho Kim; Dae‑Kyung Kang (Probiotics and Antimicrobial Proteins, 2026)

Role of CRM1-mediated SFPQ/S100A8 complex formation in psoriasis - Geunyeong Kim; Yujin Hong; Ji-Sook Lee; Juram Lee; Tae Young Han; In Sik Kim (Molecular & Cellular Toxicology, 2026)

Unveiling uncertainty in microplastic quantification: Artificial intelligence integrated Raman analysis - Min Young Oh; In-Chun Jeong; Kihyun Kim; Jeein Hong; Minseon Ju; Jaebum Choo; Ji-Hyun Kim; Sungguan Hong (Journal of Hazardous Materials, 2026)

Single-atom Cu-N/O aerogel nanozymes with dual enzymatic activities for point-of-care detection of multiple neurotransmitters - Thinh Viet Dang; Hyun Uk Lee; Ji-In Park; Jong-Seong Bae; Moon Il Kim (Chemical Engineering Journal, 2026)

Pollution characteristics of PM2.5 and PM1.0 at urban and background sites in South Korea: Focusing on health risks of PAHs and heavy metals - Sang-Jin Lee; Ho-Young Lee; In-Gyu Cho; Seong-Joon Kim; Ji Yi Lee; Hye-Jung Shin; Young Sung Ghim; Yong Pyo Kim; Sung-Deuk Choi (Atmospheric Environment, 2026)

Development of an aptamer-based diagnostic method targeting PRRSV-induced cytopathic effects - In-Hwan Oh; Phat-Loc Nguyen; Dae-Young Park; Jin-Pyo Lee; Woo-Ri Shin; Su-Min Lee; Jiho Min; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Effect of low-temperature storage regimes on the UV-B sensitivity of apple anthocyanin - Shucheng Duan; Ji Hye Kim; Min-Jea Kim; Chan Saem Gil; In-Kyu Kang; Seok Hyun Eom (Postharvest Biology and Technology, 2026)

Digital-twin tool for a drinking water distribution system using augmented reality and EPANET - Ji-Ye Park; Kwang-Ju Kim; Minhyuk Jeung; In-Su Jang; Jung-Won Yu; Mi-Seon Kang; Hyun-Su Bae; Changyoon Jeong; Sang-Soo Baek (Environmental Modelling & Software, 2026)

Development of carbon monoxide-tolerant fluorescent reporter system functional under anoxic conditions in Eubacterium callanderi KIST612 - Tantri Ardiwinata; Byeongchan Kang; Ji-Yeon Kim; Soyoung Oh; In Seop Chang (Bioresource Technology, 2026)

Antiplatelet activity of Alisma orientale extract through inhibiting glycoprotein VI and its downstream signaling pathways - Yeon-Ji Kim; Tae In Kim; Hado Choi; Kyungho Kim (Molecular & Cellular Toxicology, 2026)

Future variability in groundwater-surface water interactions: Implications for streamflow and its components using SWAT-MODFLOW 6 and CMIP 6 projections - Suh-Ho Lee; Hye-Ji Kim; In-Hee Cho; Seong-Sun Lee; Hyemin Park; Youn-Tae Kim; MoonSu Kim; Kang-Kun Lee (Journal of Hydrology, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Physiologically based pharmacokinetic modeling for umbelliferone in rats and humans: impact of extrahepatic phase II metabolism and hepatic/gut first-pass extraction on oral bioavailability and systemic disposition - Ji-Su Kong; Seong-Wook Seo; Taeyoung Kim; Hyung Ryong Moon; Jin-Wook Yoo; Min-Soo Kim; Hwayoung Yun; Seonghwan Hwang; Ee Taek Hwang; Yunjin Jung; In-Soo Yoon (Journal of Pharmaceutical Investigation, 2026)

Chemical constituents of culture broth of the marine-derived fungus Towyspora aestuari and their antioxidant activity - Mungyeong Gwon; Dae-Won Ki; Dae-Cheol Choi; Ji-Yul Kim; Won-Gi Seo; Yongkuk Lee; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2025)

Integrated VOC and non-VOC profiling for stage-specific quality assessment of kimchi fermentation using LC-MS/MS and GC-IMS - Ji Young Jeong; Min Ji Kim; Hyun-Sung Kim; Jong-Hee Lee; In Min Hwang (Food Chemistry, 2025)

Plant hormones interact to control postharvest quality in cut Rosa hybrida L. flowers and resistance to Botrytis cinerea - Suong Tuyet Thi Ha; Ji Yeong Ham; Yong-Tae Kim; Byung-Chun In (Horticulture, Environment, and Biotechnology, 2025)

Genetic mapping of tomato mutants using InDel markers between S. pimpinellifolium and two S. lycopersicum cultivars - Smita Mirsyad Warsadiharja; Shandra Amarillis; Jung Heo; Seunghye Park; Hye-yeong Kang; Yong Jun Kim; Junwoo Lee; Kang Il Cha; Eun Song Lee; Ji In Jang; A-ra Joh; Keunhwa Kim; et al. (Plant Biotechnology Reports, 2025)

3D liver model for assessing immune-mediated hepatotoxicity from biopharmaceutical risks - Mi-lang Kyun; Duhyeon Park; Hyewon Jung; Ji Hyeon Ryu; Inhye Kim; Seo Yule Jeong; Jeongha Kim; Minseong Jo; Ji-In Kwon; Ju-Kang Kim; Dahong Kim; Su A. Park; et al. (Chemical Engineering Journal, 2025)

Assessment of mechanisms and efficiencies for Mn decrease at unit processes in passive treatment facilities for mine drainage - Hye-Lim Kwon; Duk-Min Kim; Seong-Sook Park; Ji-Hye Hong; Ju-In Ko (Environmental Geochemistry and Health, 2025)

Enhanced oral bioavailability of pranlukast by preparing amorphous solid dispersion via hot-melt extrusion - Dong-Hyeon Ha; Eun-Sol Ha; Heejun Park; Seon-Kwang Lee; Ji-Su Jeong; Hui-Taek Kang; Kyu-Tae Kang; In-hwan Baek; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2025)

A novel mechanistic model for diagnosing the general health status of kimchi cabbage using the discrete-pixel data - Sang-Deok Lee; You Jin Lim; Kyung-Hwan Yeo; Oak-Jin Lee; Yun-Soo Choi; Gyu Hyeon Park; Hyejin Lee; Hyo In Yoon; Taeyang Kim; Ji-Hye Moon (Computers and Electronics in Agriculture, 2025)

Development of nutrient management system based on ion-equivalent concentration ratio and ion monitoring to maintain ionic balance in closed hydroponic solution - Min-Seok Gang; Hak-Jin Kim; Tae In Ahn; Woo-Jae Cho; Sang-Hyun Lee; Ju Young Lee; Ji-Eun Hwang (Computers and Electronics in Agriculture, 2025)

Study on modulation of inflammation expression by Brassica oleracea L. leaves extract - Jung-Wook Kang; Dan-Hee Yoo; Hyo-Min Kim; Ji-Won Hur; Kyeung-A Kwon; Kyung-Eun Lee; Min-Yeong Kim; Yong-Jun Kwon; Su-Bin Yu; Ju-Hyun Park; In-Chul Lee (Phytochemistry Letters, 2025)

Transcriptomic analysis revealed the adaptations of Latilactobacillus sakei to the cold conditions of kimchi fermentation - Min Ji Kim; Ji Young Jeong; Hyun-Sung Kim; In Min Hwang; Woojin Jun; Jong-Hee Lee (Food Research International, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Floral development and phenolic compounds production in Agastache rugosa through light regulation - Yun Ji Park; Su Hyeon Lee; Hyo In Yoon; Jai-Eok Park; To Quyen Truong; Je Hyeong Jung; Jung-Seok Yang; Inkyu Park; Sang Min Kim (Planta, 2025)

Macluraparishin C Enhances Neuroprotection Against Oxidative Stress-Induced Neurodegeneration by Activating the Antioxidant/MAPK Signaling Pathway - Md Shiblee Sadik Sabuj; Md Sadikul Islam; Md Rashedunnabi Akanda; Joonseok Lee; Ryunhee Kim; Seung Hyun Lee; Ye Ji Kim; Jin Min Oh; Hyeon Gyeong Ro; In-Shik Kim; Dongchoon Ahn; Sang-Youel Park; et al. (Molecular Neurobiology, 2025)

Analysis of changes in rice yield components and vegetation indices in response to lodging timing during the grain-filling stage, lodging severity, and nitrogen fertilization - Eun-Ji Kim; Hyeok-Jin Bak; Wan-Gyu Sang; Dongwon Kwon; Sungyul Chang; Woo-Jin Im; Do-Hyun Kim; In-Ha Lee; Nam-Jin Chung; Woon-Ha Hwang (Journal of Crop Science and Biotechnology, 2025)

Effects of exogenous L-glutamic acid and supplemental LED lighting on the growth and yield of Paprika - Yong Beom Kwon; Joo Hwan Lee; Min Ji Kim; Da Young Lee; In-Lee Choi; Hyuk Sung Yoon; Yongduk Kim; Jidong Kim; Ho-Min Kang (Horticulture, Environment, and Biotechnology, 2025)

Physiological Effects of Suspended Solids on Venerupis philippinarum and Argopecten irradians - Ha-Jeong Son; Ju-Won Kim; Min-Young Sohn; Chae-yeong Ji; Su Bhin Jeong; In Gu Kim; Jung-Ha Kang; Hee Jeong Kong; Chan-Il Park; Gyoungsik Kang (Fishes, 2025)
Suspended solids are small particles transported in the water column, which can damage marine ecosystems and impair the health of aquatic organisms. This study evaluated the physiological responses of clams (Venerupis philippinarum) and Atlantic Bay scallops (Argopecten irradians) to suspended solid exposure. Four concentrations (100–1000 mg/L) were tested, with a control group maintained at 0 mg/L. At each time point (1, 2, 4, 6, 8, and 12 days), hemolymph samples were collected from five individuals per group to measure GOT, GPT, ALP, and cortisol. Exposure to suspended solids significantly increased these biochemical indicators compared with the control. Quantitative survival analysis showed that Venerupis philippinarum survival declined to 83.3% (25/30) at 500 mg/L and 76.7% (23/30) at 1000 mg/L after 5 days, while the control maintained 100% survival. In Argopecten irradians, survival remained close to 100% in most treatments, with a slight reduction to 83.3% (25/30) at 1000 mg/L. No mortality occurred in the control group without suspended solids, whereas mortality was evident under combined temperature stress and suspended solid exposure. These findings demonstrate that suspended solids induce stress responses in both species, with early mortality in Venerupis philippinarum likely caused by particle adhesion to the gills, leading to reduced respiratory efficiency.

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Mixed-linker ZIF-8 analogue membranes with improved O2/N2 and C2H4/C3H6 separation performances synthesized by evaporation-induced rapid thermal deposition - Un Ji Kim; Ik Ji Kim; Gyu-Jin Lee; Sung In Lim; Seung-Eun Nam; Kiwon Eum; Hyuk Taek Kwon (Chemical Engineering Journal, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Improved thermal stability of NbCoSn half-Heusler compounds via Sb doping-induced complementary point defect evolution - Kyuseon Jang; Poulumi Dey; Biswanath Dutta; Hail Park; Ji-Hee Son; Jeong-In Jang; Mohammed Kamran Bhat; Hanhwi Jang; Hyungsub Kim; Jungwoo Choi; Siyuan Zhang; Ruben Bueno Villoro; et al. (Chemical Engineering Journal, 2025)

Long-acting injectable delivery system comprising ordered mixed drug aggregates with deaggregating and uniformly embeddable viscoelastic -polysaccharide solutions - Jun Soo Park; Dong Gun Lee; Jin Hyuk Myung; Min Young Jeong; In Gyu Yang; Gi Yeong Lee; Ji Won Yeo; Chae Won Park; Jin Hwan Kim; Ye Bin Shin; Myoung Jin Ho; Sung Giu Jin; et al. (Carbohydrate Polymers, 2025)

Garlic as a modulator of bacterial dynamics and metabolite profiles in kimchi fermentation - Min Ji Kim; Sera Jung; Hyun-Sung Kim; Ji Young Jeong; In Min Hwang; Woojin Jun; Jong-Hee Lee (Food Bioscience, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Microbial cell viability-driven operational strategy for enhanced acetate production in syngas fermentation - Mungyu Lee; Ji-Yeon Kim; Nulee Ji; Ludovic Jourdin; Adrie J.J. Straathof; In Seop Chang (Journal of Environmental Chemical Engineering, 2025)

Evaluating the immunomodulation effects of live lactic acid bacteria from kimchi on Transwell Caco-2 monolayer permeability - Jin Yong Kang; Daun Kim; So Yeong Mun; Ji Young Jeong; Namhee Kim; In Min Hwang; Ho Myeong Kim (Food Bioscience, 2025)

Immunomodulation Effects of Porcine Cartilage Acellularized Matrix (pCAM) for Osteoarthritis Treatment - Ji Seob Kim; Hyeon Jae Kwon; In Sun Hwang; Young Hwa Lee; Kyung-Noh Yoon; Hee-Woong Yun; Jae-Hyeok Jang; Seo Jeong Kim; Zhoodatova Aiana; Seungwoo Kim; Minhee Moon; Bongki Kim; et al. (Tissue Engineering and Regenerative Medicine, 2025)

Root-Zone Cooling Effects on Growth, Physiological, and Biochemical Responses of Taraxacum coreanum Under Hydroponics - Min-Ji Kang; Seong-Nam Jang; In-Je Kang; Gyu-Sik Yang; Yun Gon Son; Jeong Yoon Kim; Eiji Goto; Ki-Ho Son (Journal of Plant Growth Regulation, 2025)

Interaction between plant hormones in response to Botrytis cinerea infection in cut flowers with differential tissue sensitivity to ethylene - Suong Tuyet Thi Ha; Ji Yeong Ham; Yong-Tae Kim; Byung-Chun In (Postharvest Biology and Technology, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

Continuous manufacturing and process analytical technology: focusing on dosage forms with improved solubility and controlled release - Su Hyun Seok; Seung-Dong Yoo; Dong‑Wook Kim; In-Ah Lee; Kyung Hyun Min; Ji-Hyun Kang; Chun-Woong Park; Ju-Young Kim; Eun-Seok Park (Journal of Pharmaceutical Investigation, 2025)

Modulation of fermentation dynamics in kimchi using Leuconostoc mesenteroides starter - Min Ji Kim; Ji Young Jeong; In Min Hwang; Jong-Hee Lee (Food Bioscience, 2025)

Correction to: PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2025)

Salinity alternation with dark treatment enhances the gel quality and quantity of carrageenan in a red alga, Chondrus crispus - Hye-In Song; Ji-Sook Park; Jang K. Kim (Aquaculture, 2025)

New dimeric 1,3-dihydroisobenzofuran from culture broth of Fennellia flavipes - Dae-Cheol Choi; Dae-Won Ki; Ji-Yul Kim; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2025)

Origin of low-δ18O olivine phenocrysts in Late Cenozoic EM2-type intraplate basalts from Jeju Island, South Korea - Ji-In Kim; Sung Hi Choi (Journal of Asian Earth Sciences, 2025)

Single oral toxicity assessment and phytochemical analysis of the Ficus erecta Thunb. Leaves extract - Yu Jin Kim; Mee-Young Lee; Hyun Ji Park; Eunjin Sohn; Woo-Young Jeon; Sae-Rom Yoo; In Suk Choi; Joo-Hwan Kim; Soo-Jin Jeong (Toxicon, 2025)

Oncheong-eum alleviated hepatic lipid accumulation and intestinal barrier disruption in nonalcoholic steatohepatitis in vivo model - Kwang-Youn Kim; Yun-Mi Kang; Tae In Kim; Yeon-Ji Kim; Kyungho Kim (Molecular & Cellular Toxicology, 2025)

Genetic dissection of resistance to Phytophthora sojae using genome-wide association and linkage analysis in soybean [Glycine max (L.) Merr.] - Hee Jin You; Ik Hyun Jang; Jung-Kyung Moon; In-Jeong Kang; Ji-Min Kim; Sungtaeg Kang; Sungwoo Lee (Theoretical and Applied Genetics, 2024)

A new quantitative method to validate the expression of homoeologous genes in polyploids - Keunhwa Kim; Eun Song Lee; Smita Mirsyad Warsadiharja; Junwoo Lee; Hye-yeong Kang; Ji In Jang; Yu Seon Chae; Soon Ju Park (Plant Biotechnology Reports, 2024)

Crystalline carbon antioxidase mimics enhancing innate anti-inflammatory immunity for the treatment of rheumatoid arthritis - Chanhee Choi; DaBin Yim; Hyo Keun Kim; Su-Ji Jeon; In-Jun Hwang; Hongwon Kim; Yoonhee So; Sin Lee; Yejoo Yu; Yujin Choi; Hwankyu Lee; Chul-Su Yang; et al. (Chemical Engineering Journal, 2024)

A new neo-lignan from culture broth of Phellinus linteus and its dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Ji-Yul Kim; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Exploring flavor perception through metabolite profiling and sensory approaches during starter kimchi fermentation - Moeun Lee; Daun Kim; In Min Hwang; Ji Yoon Chang (Food Bioscience, 2024)

Inulae Flos has Anti-Depressive Effects by Suppressing Neuroinflammation and Recovering Dysfunction of HPA-axis - Jin Se Kim; Jin Hee Kim; Hyeyoon Eo; In Gyoung Ju; So-ri Son; Ji-Woon Kim; Dae Sik Jang; Myung Sook Oh (Molecular Neurobiology, 2024)

Cheong-sang-gyeon-tong-tang improves hepatic steatosis by regulating cholesterol metabolism - Yun-Mi Kang; Kwang-Youn Kim; Tae In Kim; Yeon-Ji Kim; Han-Hae Kim; Kyungho Kim (Molecular & Cellular Toxicology, 2024)

Comparison of biogenic volatile organic compounds emissions from representative urban tree species in South Korea and evaluation of standard emission rate models - Da-Hyun Baek; Ye-Bin Seo; Seong-Ji Yu; In-Young Choi; Sang-Woo Lee; Youn-Suk Son; Trieu-Vuong Dinh; Jo-Chun Kim (Atmospheric Environment, 2024)

Carboxymethyl cellulose-based rotigotine nanocrystals-loaded hydrogel for increased transdermal delivery with alleviated skin irritation - Jun Soo Park; Jae Hee Seo; Min Young Jeong; In Gyu Yang; Ji Seong Kim; Jin Hwan Kim; Myoung Jin Ho; Sung Giu Jin; Min Koo Choi; Yong Seok Choi; Myung Joo Kang (Carbohydrate Polymers, 2024)

Polyhexamethylene guanidine phosphate induces pyroptosis via reactive oxygen species-regulated mitochondrial dysfunction in bronchial epithelial cells - Jun Young Park; Ji-Hee Kim; Chan Ho Park; Sung-Hwan Kim; In-Hyeon Kim; Won Gil Cho (Toxicology, 2024)

Highly visible-light-active sulfur and carbon co-doped TiO2 (SC-TiO2) heterogeneous photocatalysts prepared by underwater discharge plasma - Ha-Rim An; Chaehun Lim; Chung Gi Min; Byoungchul Son; Chang-Yeon Kim; Ji-In Park; Jong Pil Kim; Yesul Jeong; Jiwon Seo; Moonsang Lee; Jihyang Park; Young-Seak Lee; et al. (Chemosphere, 2024)

Correction to: Microbacterium aquilitoris sp. nov. and Microbacterium gawkjiense sp. nov., isolated from beach - Soon Dong Lee; Hong Lim Yan; Ji-Sun Kim; In Seop Kim (Archives of Microbiology, 2024)

A comprehensive systematic review and meta-analysis of Listeria monocytogenes prevalence in food products in South Korea - Hyeon Ji Je; Ui In Kim; Ok Kyung Koo (International Journal of Food Microbiology, 2024)

Dry reforming process using microwave plasma generator with high carbon dioxide conversion efficiency for syngas production - Chang Hyun Cho; Ji Hun Kim; Jong Keun Yang; In Sun Park; Yong-Sup Choi; In Je Kang (Fuel, 2024)

Two-in-one strategy: Discretely functionalized electrolyte additive for stable lithium metal batteries coupled with Ni-rich cathode - Yong Min Kim; Jeong In Choi; Bo Keun Park; Ji Woo Han; Jong-Won Lee; Hyun-seung Kim; Ki Jae Kim (Chemical Engineering Journal, 2024)

Low-dose-rate gamma radiation aggravates titanium dioxide nanoparticle-induced lung injury in mice - Sohi Kang; Hae-June Lee; Yeonghoon Son; Min Ji Bae; Wol Soon Jo; Jun Hong Park; Sohee Jeong; Changjong Moon; In-Sik Shin; Chang Geun Lee; Joong Sun Kim (Molecular & Cellular Toxicology, 2024)

Distributions of PCDD/Fs, PCBs, and PCNs in coastal sediments collected from major industrial bays in South Korea - Ji-Young Son; Sanjenbam Nirmala Khuman; Min-Kyu Park; Ho-Young Lee; Chul-su Kim; In-Seok Lee; Sung-Deuk Choi (Marine Pollution Bulletin, 2024)

High-performance interfacial water evaporation of black TiO2-x with high-concentration bulk oxygen vacancies - Myeongjun Ji; Jeong Hyun Kim; Hee Yeon Jeon; Seungheon Han; Dong Hoon Lee; Young-In Lee (Chemical Engineering Journal, 2024)

Microbacterium aquilitoris sp. nov. and Microbacterium gwkjiense sp. nov., isolated from beach - Soon Dong Lee; Hong Lim Yang; Ji-Sun Kim; In Seop Kim (Archives of Microbiology, 2024)

TRIAD method to assess ecological risks of contaminated soils in abandoned mine sites - Dokyung Kim; Jin Il Kwak; Tae-Yang Lee; Lia Kim; Haemi Kim; Sun Hwa Nam; Wonjae Hwang; June Wee; Yong Ho Lee; Songhee Kim; Ji-In Kim; Sunhee Hong; et al. (Journal of Hazardous Materials, 2024)

Particulate matter-mediated oxidative stress induces airway inflammation and pulmonary dysfunction through TXNIP/NF-κB and modulation of the SIRT1-mediated p53 and TGF-β/Smad3 pathways in mice - Ji-Hye Ha; Ba-Wool Lee; Da-Hye Yi; Se-Jin Lee; Woong-Il Kim; So-Won Pak; Hyeon-Young Kim; Sung-Hwan Kim; In-Sik Shin; Jong-Choon Kim; In-Chul Lee (Food and Chemical Toxicology, 2024)

Development of an In Vitro Model for Inflammation Mediated Renal Toxicity Using 3D Renal Tubules and Co-Cultured Human Immune Cells - Mi-lang Kyun; Tamina Park; Hyewon Jung; Inhye Kim; Ji-In Kwon; Seo Yule Jeong; Myeongjin Choi; Daeui Park; Yu Bin Lee; Kyoung-Sik Moon (Tissue Engineering and Regenerative Medicine, 2023)

Performance analysis of heat pipe-based passive in-core decay heat removal system for the small modular reactor design with MARS-KS code - Ji Yong Kim; Ye Yeong Park; In Cheol Bang (Annals of Nuclear Energy, 2023)

Efficient MAPbI3-based perovskite solar cells exceeding 21% efficiency via aging treatment - Dae Woo Kim; Young Wook Noh; Jongmin Han; Hye Seung Kim; Chung Hyeon Jang; Ji A. Hong; Sangmi Park; Min Hyeong Lee; Ye In Kim; Myoung Hoon Song (Chemical Engineering Journal, 2023)

Suppression of TBCK enhances TRAIL-mediated apoptosis by causing the inactivation of the akt signaling pathway in human renal carcinoma Caki-1 cells - Cho-Young Park; Ji-Hoon Jang; In-Hwan Song; Joo-Young Kim; Kyung-Oh Doh; Tae-Jin Lee (Genes & Genomics, 2023)

Mycotoxins in food and feed: toxicity, preventive challenges, and advanced detection techniques for associated diseases - Debasish Kumar Dey; Ji In Kang; Vivek K. Bajpai; Kwanwoo Kim; Hoomin Lee; Sonam Sonwal; Jesus Simal-Gandara; Jianbo Xiao; Sajad Ali; Yun Suk Huh; Yong-Kyu Han; Shruti Shukla (Critical Reviews in Food Science and Nutrition, 2023)

Chemical constituents of the culture broth of Dentipellis fragilis and their anti-inflammatory activities - Dae-Won Ki; Chae-Won Kim; Dae-Cheol Choi; Gun-Woo Oh; Thi-Phuong Doan; Ji-Yul Kim; Won-Keun Oh; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry, 2023)

Led-mediated instantaneous pore formation in membranes driven by structural transformation and deprotonation of phospholipids - Hui Bang Cho; Hye Jin Kim; Hye-Ryoung Kim; Sujeong Lee; Ji-In Park; Keun-Hong Park (Chemical Engineering Journal, 2023)

Neuregulin-1 suppresses anti-apoptotic effect of Der p 38 on neutrophils by inhibition of cytokine secretion - Yujin Hong; Ji Hyeon Choi; Min Hwa Hong; Geunyeong Kim; Ji-Sook Lee; Ran-Sook Woo; Eun Ju Yang; In Sik Kim (Molecular & Cellular Toxicology, 2023)

NME1 functions as a metastasis suppressor in pancreatic cancer - Do Yeon Kim; Hyeseon Yun; Ji-Eun You; Dong-In Koh; Yea Seong Ryu; Dong-Il Yoon; Chul Hee Kim; Ji-U Lee; Dong- Hee Kang; Dong-Hoon Jin (Molecular & Cellular Toxicology, 2023)

Association between SYVN1 and SEL1 genetic polymorphisms and remission in rheumatoid arthritis patients treated with TNF-α inhibitors: a machine learning approach - Woorim Kim; Ha Rim Yeon; Jun Hyeob Kim; Joo Hee Kim; Ji Hyoun Kim; Hyoun-Ah Kim; Ju-Yang Jung; Jinhyun Kim; In Ah Choi; Kyung Eun Lee (Immunologic Research, 2023)

Quantification and health risk assessment of ochratoxin A in dried fruit, spices, and coffee - In Min Hwang; Ji Young Jeong; Boyeon Park; Ji Yeon Choi; Naeem Khan; Nargis Jamila; Bo Ryun Yoon; Jae Sung Kim (Food Additives & Contaminants: Part A, 2023)

Safety concerns regarding impurities in L-Tryptophan associated with eosinophilia myalgia syndrome - Soo Min Ko; Ji-Eun Park; In Kyung Heo; Yong Uk Shin; Yang Hee Kim; Woo-Chan Son (Food and Chemical Toxicology, 2023)

Recent advances in engineering aptamer-based sensing and recovery of heavy metals and rare earth elements for environmental sustainability - Woo-Ri Shin; Gna Ahn; Jin-Pyo Lee; In-Hwan Oh; Ji-Young Ahn; Yang-Hoon Kim; Soryong Chae (Chemical Engineering Journal, 2023)

Acetogen and acetogenesis for biological syngas valorization - Ji-Yeon Kim; Mungyu Lee; Soyoung Oh; Byeongchan Kang; Muhammad Yasin; In Seop Chang (Bioresource Technology, 2023)

Mechanisms of interactions in pattern-recognition of common glycostructures across pectin-derived heteropolysaccharides by Toll-like receptor 4 - Gyu Hwan Hyun; In Ho Cho; Yoon Young Yang; Da-Hye Jeong; Yun Pyo Kang; You-Sun Kim; Seul Ji Lee; Sung Won Kwon (Carbohydrate Polymers, 2023)

Hospital admission risks and excess costs for neurological symptoms attributable to long-term exposure to fine particulate matter in New York State, USA - Jieun Min; Whanhee Lee; Michelle L. Bell; Yijun Kim; Seulkee Heo; Ga Eun Kim; Jee Hyun Kim; Ji Young Yun; Soo In Kim; Joel Schwartz; Eunhee Ha (Environmental Research, 2023)

Estuarine dam water discharge enhances summertime primary productivity near the southwestern Korean coast - Dongyoung Kim; Rubao Ji; Zhixuan Feng; Jaebin Jang; Dae-In Lee; Won Chan Lee; Chang-Keun Kang (Marine Pollution Bulletin, 2023)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Biochemical responses and phytoremediation potential of Azolla imbricata (Roxb.) Nakai in water and nutrient media exposed to waste metal cutting fluid along with temperature and humidity stress - Sivakumar Subpiramaniyam; Sung-Chul Hong; Pyong-In Yi; Seong-Ho Jang; Jeong-Min Suh; Eun-Sang Jung; Je-Sung Park; Velmurugan Palanivel; Young-Chae Song; Lae-Hyeon Cho; Young-Hoon Park; Ji-Suk Kim (Journal of Hazardous Materials, 2023)

Chemical and morphological characterization by SEM–EDS of PM2.5 collected during winter in Ulaanbaatar, Mongolia - Ji-In Park; Min Sung Kim; Myoung Yeo; Mira Choi; Ji Yi Lee; Amgalan Natsagdorj; Changhyuk Kim; Mijung Song; Kyoung-Soon Jang (Atmospheric Environment, 2023)

Correction: Antioxidant activity of edible sprouts and phytosterol contents by HPLC/UV analysis - Juree Kim; Ji Hyun Kim; Se In Bang; Hanna Shin; Eun Ju Cho; Sanghyun Lee (Horticulture, Environment, and Biotechnology, 2023)

Emplacement ages and petrogenesis of the Sunchang and Namwon granitoids, South Korea - Sung Hi Choi; Ji-In Kim (Lithos, 2023)

Hf isotope compositions of basaltic rocks from Jeju Island, South Korea: Implications for the origin of the dichotomous isotopic distribution of late Cenozoic magmatism in East Asia - Ji-In Kim; Sung Hi Choi; Der-Chuen Lee (Lithos, 2023)

Construction of an underwater plasma and Fenton hybrid system for the rapid oxidation of organic dyes and antibiotics - Soo Hyeon Kim; Jiwon Seo; Yongcheol Hong; Yongwook Shin; Hea-Jong Chung; Ha-Rim An; ChangYeon Kim; Ji-In Park; Hyun Uk Lee (Journal of Water Process Engineering, 2023)

Effects of edible insect extracts on the antioxidant, physiochemical, and microbial properties of Tteokgalbi during refrigerated storage - Hae In Yong; Tae-Kyung Kim; Ji Yoon Cha; Jae Hoon Lee; Min-Cheol Kang; Samooel Jung; Yun-Sang Choi (Food Bioscience, 2023)

A rice seed-specific glycine-rich protein OsDOR1 interacts with GID1 to repress GA signaling and regulates seed dormancy - Sooyeon Kim; Sun Mi Huh; Hay Ju Han; Gang Seob Lee; Yong-Sic Hwang; Mi Hyun Cho; Beom-Gi Kim; Ji Sun Song; Joo Hee Chung; Myung Hee Nam; Hyeonso Ji; Kyung-Hwan Kim; et al. (Plant Molecular Biology, 2023)

A highly efficient and versatile genetic engineering toolkit for a methanotroph-based biorefinery - Jiyeong Jeong; Tae Hyun Kim; Nulee Jang; Minji Ko; Seong Keun Kim; Ji In Baek; Georgii Emelianov; Eugene Rha; Kil Koang Kwon; Haseong Kim; Eun Yeol Lee; Dae-Hee Lee; et al. (Chemical Engineering Journal, 2023)

Sargassum horneri and Ascophyllum nodosum extracts enhance thermal tolerance and antioxidant activity of Neopyropia yezoensis - Sol Han; Hye-In Song; Ji-Sook Park; Youn-Jung Kim; Schery Umanzor; Charles Yarish; Jang K. Kim (Journal of Applied Phycology, 2023)

Peptides inhibiting angiotensin-I-converting enzyme: Isolation from flavourzyme hydrolysate of Protaetia brevitarsis larva protein and identification - Jae Hoon Lee; Tae-Kyung Kim; Hae In Yong; Ji Yoon Cha; Kyung-Mo Song; Hyo Geun Lee; Jun-Geon Je; Min-Cheol Kang; Yun-Sang Choi (Food Chemistry, 2023)

Clean power generation from salinity gradient using reverse electrodialysis technologies: Recent advances, bottlenecks, and future direction - Soryong Chae; Hanki Kim; Jin Gi Hong; Jaewon Jang; Mitsuru Higa; Mohammad Pishnamazi; Ji-Yeon Choi; Ramali Chandula Walgama; Chulsung Bae; In S. Kim; Jin-Soo Park (Chemical Engineering Journal, 2023)

Correction: Cardiac biomarkers and detection methods for myocardial infarction - Sang Young Kim; Jin-Pyo Lee; Woo-Ri Shin; In-Hwan Oh; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2023)

3-Hydroxymorphinan protects against hypoxia-induced cell death in primary astrocyte by regulating Ca2+ influx and the glutamate homeostasis - Ok-Hyeon Kim; Gyeong Yun Lee; Kyung Yong Kim; Jong In Son; Tae Woo Jung; Ji Hoon Jeong; Joon Seok Bang; Hyoung-Chun Kim; Yoon Hee Chung; Hyun Jung Lee (Molecular & Cellular Toxicology, 2023)

Clinical features and epidemiology of severe fever with thrombocytopenia syndrome in dogs in the Republic of Korea: an observational study (2019–2020) - Sun-Woo Han; Ye-In Oh; Ji-Min Rim; Yoon-Kyoung Cho; Dong-Hoo Kim; Jun-Gu Kang; Kyoung-Seong Choi; Joon-Seok Chae (Veterinary Research Communications, 2022)

The present and future of minimally invasive methods for Alzheimer's disease diagnosis - In-Hwan Oh; Woo-Ri Shin; JinHee Ahn; Jin-Pyo Lee; Jiho Min; Ji-Young Ahn; Yang-Hoon Kim (Toxicology and Environmental Health Sciences, 2022)

Cardiac biomarkers and detection methods for myocardial infarction - Sang Young Kim; Jin-Pyo Lee; Woo-Ri Shin; In-Hwan Oh; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2022)

Antioxidant activity of edible sprouts and phytosterol contents by HPLC/UV analysis - Juree Kim; Ji Hyun Kim; Se In Bang; Hanna Shin; Eun Ju Cho; Sanghyun Lee (Horticulture, Environment, and Biotechnology, 2022)
This study evaluated the in vitro radical scavenging activities of edible tree sprouts, particularly those of the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH), hydroxyl radical, and singlet oxide radical, to assess their antioxidant activities. Additionally, stigmasterol (ST) and β-sitosterol (BS) were analyzed using HPLC/UV. The edible sprouts of Eleutherococcus senticosus (ESC) and Morus alba (MAB) exhibited the highest DPPH scavenging activity among other edible sprouts. A reverse-phase column was used in an isocratic elution system, after which UV detection was performed at 210 nm. ST and BS analyses indicated that ESC sprouts contained the highest amounts of ST (9.99 mg·g − 1 extract), whereas MAB sprouts contained the highest concentrations of BS (14.69 mg·g − 1 extract). In conclusion, the highest antioxidant activity was observed in the edible sprouts with the highest phytosterol content. Therefore, our findings provide a theoretical basis for the development of plant-based functional foods or supplements with antioxidant properties.

Evaluation of residual level and distribution characteristics of organochlorine pesticides in agricultural soils in South Korea - Sung-Mi Yun; Jeong-ki Yoon; Ji-In Kim; In Ja Kim; Hyun-Koo Kim; Hyen-Mi Chung; Dong-Jin Kim; Hoe-Jung Noh (Environmental Science and Pollution Research, 2022)

Daldinans D‒G, new isoindolinone antioxidants isolated from the ascomycete Daldinia concentrica - Dae-Won Ki; Seong-Eun Kim; Ji-Yul Kim; Ja-Gyeong Song; Byung Soon Hwang; In-Kyoung Lee; Bong-Sik Yun (Journal of Natural Medicines, 2022)

Neferine increases sensitivities to multiple anticancer drugs via downregulation of Bcl-2 expression in renal cancer cells - Eun-Ae Kim; Ji Hoon Jang; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Ho-Yong Sohn; Tae-Jin Lee (Genes & Genomics, 2022)

Galuteolin, identified in the extract of thymus quinquecostatus flowers, is involved in inhibiting melanin biosynthesis in B16/F10 melanoma cells - Mi-Hee Kim; Bora Kwon; Kwang-Sang Kim; Min-Sook Kim; Min-Ji Kim; Hwa-Jin Kim; Da-In Choi; Miyeon Park; Moosung Kim; Min-Kyu Shin; Seung-Il Jeong; Kang-Yeol Yu; et al. (Natural Product Research, 2021)

The optimal standard protocols for whole-genome sequencing of antibiotic-resistant pathogenic bacteria using third-generation sequencing platforms - Tae-Min La; Ji-hoon Kim; Taesoo Kim; Hong-Jae Lee; Yoonsuk Lee; Hyunjin Shin; Yongjun Song; Gyuhee Ahn; Won Hur; Joong-Bok Lee; Seung-Yong Park; In-Soo Choi; et al. (Molecular & Cellular Toxicology, 2021)

Anti-inflammatory activity of palmitoylethanolamide ameliorates osteoarthritis induced by monosodium iodoacetate in Sprague–Dawley rats - Jae In Jung; Hyun Sook Lee; Young Eun Jeon; So Mi Kim; Su Hee Hong; Joo Myung Moon; Cho Young Lim; Yoon Hee Kim; Eun Ji Kim (Inflammopharmacology, 2021)
Novel treatment strategies are urgently required for osteoarthritis (OA). Palmitoylethanolamide (PEA) is a naturally occurring fatty acid amide with analgesic and anti-inflammatory effects. We aimed to examine its effect on OA and elucidate the molecular mechanism of actions in monosodium iodoacetate (MIA)-induced OA Sprague–Dawley rats. The experimental animals were divided into normal control group (injected with saline + treated with phosphate-buffered saline (PBS), NOR), control group (injected with MIA + treated with PBS, CON), 50 or 100 mg/kg body weight (BW)/day PEA-treated group (injected with MIA + treated with 50 or 100 mg of PEA/kg BW/day, PEA50 or PEA100), and positive control group (injected with MIA + treated with 6 mg of diclofenac/kg BW/day, DiC). The changes in blood parameters, body parameters, gene expression of inflammatory mediators and cytokines, knee thickness, and joint tissue were observed. Oral administration of PEA had no adverse effects on the BW, liver, or kidneys. PEA reduced knee joint swelling and cartilage degradation in MIA-induced OA rats. The serum levels of leukotriene B4, nitric oxide, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and prostaglandin E2 considerably reduced in the PEA100 group compared with those in the CON group. In the synovia of knee joints, the mRNA expression of iNOS , 5-Lox , Cox-2 , Il-1β , Tnf-α , and Mmp-2 , -3 , -9 , and -13 apparently increased with MIA administration. Meanwhile, Timp-1 mRNA expression apparently decreased in the CON group but increased to the normal level with PEA treatment. Thus, PEA can be an effective therapeutic agent for OA.

Lactucin induces apoptosis through reactive oxygen species-mediated BCL-2 and CFLARL downregulation in Caki-1 cells - Ji Hoon Jang; Cho-Young Park; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Chuleui Jung; Ho-Yong Sohn; Tae-Jin Lee (Genes & Genomics, 2021)

Overexpression of Arabidopsis thaliana blue-light inhibitor of cryptochromes 1 gene alters plant architecture in soybean - Hyun Suk Cho; Yoon Jeong Lee; Hye Jeong Kim; Moon-Young Park; Wan Woo Yeom; Ji Hyeon Song; In Ah Kim; Seong-Hyeon Kim; Jeong-Il Kim; Young-Soo Chung (Plant Biotechnology Reports, 2021)

Duganella aceris sp. nov., isolated from tree sap and proposal to transfer of Rugamonas aquatica and Rugamonas rivuli to the genus Duganella as Duganella aquatica comb. nov., with the emended description of the genus Rugamonas - Dabin Jeon; In Seop Kim; Hanna Choe; Ji-Sun Kim; Soon Dong Lee (Archives of Microbiology, 2021)

Temporal variation of sulfate concentration in PM2.5 and major factors enhancing sulfate concentration in the atmosphere of Seoul, Korea - Na Kyung Kim; In Sun Kim; In Ho Song; Seung Myung Park; Hyung Bae Lim; Yong Pyo Kim; Hye Jung Shin; Ji Yi Lee (Air Quality, Atmosphere & Health, 2021)

Genetic analysis and population genetic structure of hard-shelled mussel, Mytilus coruscus Gould 1861 (Mytiloida: Mytilidae) from the coasts of South Korea based on mitochondrial cytochrome oxidase (COI) gene sequences - Chang Ho Yi; Moongeun Yoon; Ji Min Kim; Il-Hun Kim; In-Young Cho; Hye Suck An (Genes & Genomics, 2021)

Source identification and assessment of heavy metal contamination in urban soils based on cluster analysis and multiple pollution indices - Hong-gil Lee; Hyun-Koo Kim; Hoe-Jung Noh; Yoon Joo Byun; Hyen-Mi Chung; Ji-In Kim (Journal of Soils and Sediments, 2021)

KIF11 inhibition decreases cytopathogenesis and replication of influenza A virus - Dong-In Kim; Ji-Hun Kang; Eui-Ho Kim; Young-Jin Seo (Molecular & Cellular Toxicology, 2021)

Anthropogenic nitrogen is changing the East China and Yellow seas from being N deficient to being P deficient - Ji‐Young Moon; Kitack Lee; Weol‐Ae Lim; Eunil Lee; Minhan Dai; Yang‐Ho Choi; In‐Seong Han; Kyoungsoon Shin; Ja‐Myung Kim; Jinho Chae (Limnology and Oceanography, 2021)
Addition of the increased anthropogenic nitrogen (NO x and NH y ) emitted from northeast Asian countries to the Yellow and East China seas and coastal waters around Korea has resulted in an unparalleled increase in the nitrate (N) concentration relative to the phosphate (P) and silicate (Si) concentrations in the upper ocean. We found that for the Yellow Sea the increase in N over P was largely explained by increased atmospheric nitrogen deposition, whereas for the northern East China Sea, downstream of the Changjiang River plume, the trend in N increase relative to P was more associated with a change in the combined input of nutrients from atmospheric deposition and riverine discharges. In contrast, the dynamics of the N to P relationship in the southern East China Sea was largely controlled by a change in the intrusion intensity of the Kuroshio Current, which has a low N : P ratio. The disproportionate and persistent input of nutrients to the marine waters of this region over the past four decades has transformed extensive areas from being N deficient to being P deficient, and has concurrently decreased the concentration of Si relative to N. In coastal waters around Korea in particular, these shifts in the nutrient regime have been accompanied by a change from diatom‐dominated to dinoflagellate‐dominated blooms. Given the complexity of coastal ecosystems, the associations between changes in nutrient regimes and biological changes need to be investigated in other coastal areas receiving increasing loads of anthropogenic nitrogen.

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Monitoring a short-lived earthquake swarm during April–May 2020 in Haenam, Korea, and its preliminary results - Jongwon Han; Wooseok Seo; Han-Joon Kim; Won-Young Kim; Deokhee Won; Ji-In Chung; Kwang-Hee Kim (Geosciences Journal, 2021)

Resolvin D3 Promotes Inflammatory Resolution, Neuroprotection, and Functional Recovery After Spinal Cord Injury - Juri Kim; Hari Prasad Joshi; Seung Hun Sheen; Kyoung-Tae Kim; Jae Won Kyung; Hyemin Choi; Ye Won Kim; Su Yeon Kwon; Eun Ji Roh; Un Yong Choi; Seil Sohn; Yong Ho Kim; et al. (Molecular Neurobiology, 2021)

Environmental monitoring of toxic metals in roadside soil and dust in Ulsan, South Korea: pollution evaluation and distribution characteristics - Ji-Hyun Kim; Jung-In Sohn; Seok-Young Oh (Environmental Monitoring and Assessment, 2020)

Biological activities and chemical components of Potentilla kleiniana Wight & Arn - Song Hua Xuan; In Ki Hong; Yun Ju Lee; Ji Woong Kim; Soo Nam Park (Natural Product Research, 2020)

Targeting X chromosome-linked inhibitor of apoptosis protein in mucoepidermoid carcinoma of the head and neck: A novel therapeutic strategy using nitidine chloride - Hye-Jeong Kwon; Kyungsil Yoon; Ji-Youn Jung; Mi Heon Ryu; Sung-Hyun Kim; Eun-Seon Yoo; So-Young Choi; In-Hyoung Yang; Seong Doo Hong; Ji-Ae Shin; Sung-Dae Cho (Journal of Molecular Medicine, 2020)

Rahnella aceris sp. nov., isolated from sap drawn from Acer pictum - Soon Dong Lee; Dabin Jeon; In Seop Kim; Hanna Choe; Ji-Sun Kim (Archives of Microbiology, 2020)

Validation and measurement uncertainty of GC-MS quantification method for nicotine in dried mushrooms using QuEChERS extraction - Hyun-Hee Kang; Choong-in Yun; Ji-Young Moon; Joon-Goo Lee; Young-Jun Kim (Food Additives & Contaminants: Part A, 2020)

High-density linkage map reveals QTL for Type-I seed coat cracking in RIL population of soybean [Glycine max (L.) Merr.] - Beom Kyu Kang; Jeong Hyun Seo; Hyun Jo; Krishnanand P. Kulkarni; Man Soo Choi; Hyun Tae Kim; Jeong Dong Lee; Sanjeev K. Dhungana; Hong Sik Kim; Jae Hyeon Oh; Ji Hee Park; Sang Ouk Shin; et al. (Euphytica, 2020)
Seed coat cracking (SCC), particularly the Type-I irregular cracking, is critical in determining the quality of appearance and commercial value of soybean seeds. The objective of this study was to identify the quantitative trait loci (QTLs) for SCC with high-density genetic map. One hundred sixty-seven recombinant inbred lines (RILs) developed from a cross between Uram (SCC-resistant) and Chamol (SCC-susceptible) were evaluated for SCC over 2 years (2016–2017). The QTL analysis identified 12 QTLs located on chromosomes 2 (D1b), 6 (C2), 8 (A2), 9 (K), 10 (O), 12 (H), 19 (L), and 20 (I). Out of the 12 QTLs, qSC2-1 , qSC9, SC10-1 , qSC10-2 , and qSC12 were novel QTLs and the other seven QTLs ( qSC2-2 , qSC2-3 , qSC6 , qSC8 , qSC19-1 , qSC19-2 , and qSC20 ) were found to co-localize with the previously identified QTLs. The mean SCC of the RILs of early maturity group was significantly higher than that of the late maturity group, suggesting an association between SCC and maturity loci. In addition, although 10 QTLs were distantly located from the maturity loci ( E1 , E3 , E4 , E7 , and E10 ), qSC10-1 and qSC10-2 co-localized with the maturity loci E2 . The results obtained in this study provide useful genetic information on SCC which could be used in the SCC breeding programs.

High-throughput phenotyping platform for analyzing drought tolerance in rice - Song Lim Kim; Nyunhee Kim; Hongseok Lee; Eungyeong Lee; Kyeong-Seong Cheon; Minsu Kim; JeongHo Baek; Inchan Choi; Hyeonso Ji; In Sun Yoon; Ki-Hong Jung; Taek-Ryoun Kwon; et al. (Planta, 2020)
Main conclusion A new imaging platform was constructed to analyze drought-tolerant traits of rice. Rice was used to quantify drought phenotypes through image-based parameters and analyzing tools. Abstract Climate change has increased the frequency and severity of drought, which limits crop production worldwide. Developing new cultivars with increased drought tolerance and short breeding cycles is critical. However, achieving this goal requires phenotyping a large number of breeding populations in a short time and in an accurate manner. Novel cutting-edge technologies such as those based on remote sensors are being applied to solve this problem. In this study, new technologies were applied to obtain and analyze imaging data and establish efficient screening platforms for drought tolerance in rice using the drought-tolerant mutant osphyb . Red–Green–Blue images were used to predict plant area, color, and compactness. Near-infrared imaging was used to determine the water content of rice, infrared was used to assess plant temperature, and fluorescence was used to examine photosynthesis efficiency. DroughtSpotter technology was used to determine water use efficiency, plant water loss rate, and transpiration rate. The results indicate that these methods can detect the difference between tolerant and susceptible plants, suggesting their value as high-throughput phenotyping methods for short breeding cycles as well as for functional genetic studies of tolerance to drought stress.

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Strong alkaline condition is preferable for producing 7,10-dihydroxy-8(E)-hexadecenoic acid from palmitoleic acid by Pseudomonas aeruginosa KNU-2B - Ji-Sun Moon; Yeon-Jung Lee; In-Hwan Kim; Hak-Ryul Kim (Biotechnology Letters, 2020)

Production of 7,10,12-trihydroxy-8(E)-octadecenoic acid from ricinoleic acid by Pseudomonas aeruginosa KNU-2B - Yeon-Jung Lee; Ji-Sun Moon; In-Hwan Kim; Hak-Ryul Kim (Biotechnology Letters, 2020)

Characterization of Cellobiohydrolases from Schizophyllum commune KMJ820 - Sanath Kondaveeti; Sanjay K. S. Patel; Janghun Woo; Ji Hyang Wee; Sang-Yong Kim; Riyadh I. Al-Raoush; In-Won Kim; Vipin Chandra Kalia; Jung-Kul Lee (Indian Journal of Microbiology, 2020)

An inverse agonist of estrogen-related receptor γ regulates 2-arachidonoylglycerol synthesis by modulating diacylglycerol lipase expression in alcohol-intoxicated mice - Yoon Seok Jung; Yong-Hoon Kim; Kamalakannan Radhakrishnan; Jina kim; Don-Kyu Kim; Ji-Hyeok Lee; Hyunhee Oh; In-Kyu Lee; Wook Kim; Sung Jin Cho; Cheol Soo Choi; Steven Dooley; et al. (Archives of Toxicology, 2020)

Harvest strategies to maximize the annual production of bioactive compounds, glucosinolates, and total antioxidant activities of kale in plant factories - Hyo In Yoon; Ji-Soo Kim; Damin Kim; Chul Young Kim; Jung Eek Son (Horticulture, Environment, and Biotechnology, 2019)

The medicinal mushroom Auricularia auricula - judae (Bull.) extract has antioxidant activity and promotes procollagen biosynthesis in HaCaT cells - Young-Ji Choi; In-Sun Park; Mi-Hee Kim; Bora Kwon; Young-Moo Choo; Seung-Il Jeong; Kang-Yeol Yu; Chung Hyeon Choe; Jiyoung Kim (Natural Product Research, 2019)

Paenibacillus lutimineralis sp. nov., Isolated From Bentonite - Eui-Sang Cho; In-Tae Cha; Dong-Ho Seo; Young-Do Nam; Seong Woon Roh; Jae-Hwan Kim; Myung-Ji Seo (Current Microbiology, 2019)

Trpm2 Ablation Accelerates Protein Aggregation by Impaired ADPR and Autophagic Clearance in the Brain - Yongwoo Jang; Byeongjun Lee; Hyungsup Kim; Seungmoon Jung; Sung Hoon Lee; So-Young Lee; Ji Hyun Jeon; In-Beom Kim; Seo-Ho Lee; Byung-Ju Kim; Uh-Hyun Kim; Yunjong Lee; et al. (Molecular Neurobiology, 2019)

PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2019)
Impaired neurogenesis has been associated with several brain disorders, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The role of peroxiredoxin 6 (PRDX6) in neurodegenerative diseases is very controversial. To demonstrate the role of PRDX6 in neurogenesis, we compared the neurogenesis ability of PRDX6-overexpressing transgenic (Tg) mice and wild-type mice and studied the involved molecular mechanisms. We showed that the neurogenesis of neural stem cells (NSCs) and the expression of the marker protein were lower in PRDX6 Tg-mice than in wild-type mice. To determine the factors involved in PRDX6-related neural stem cell impairment, we performed a microarray experiment. We showed that the expression of WDFY1 was dramatically decreased in PRDX6-Tg mice. Moreover, WDFY1 siRNA decreases the differentiation ability of primary neural stem cells. Interestingly, WDFY1 reportedly recruits the signaling adaptor TIR-domain-containing adapter-inducing interferon-β (TRIF) to toll-like receptors (TLRs); thus, we showed the relationship among TLRs, PRDX6, and WDFY1. We showed that TLR4 was dramatically reduced in PRDX6 Tg mice, and reduced TLR4 expression and neurogenesis was reversed by the introduction of WDFY1 plasmid in the neural stem cells from PRDX6 Tg mice. This study indicated that PRDX6 inhibits the neurogenesis of neural precursor cells through TLR4-dependent downregulation of WDFY1 and suggested that the inhibitory effect of PRDX6 on neurogenesis play a role in the development of neurodegenerative diseases in the PRDX6 overexpressing transgenic mice.

Stem Cells Seeded on Multilayered Scaffolds Implanted into an Injured Bladder Rat Model Improves Bladder Function - Kshitiz Raj Shrestha; Seung Hwan Jeon; Ae Ryang Jung; In Gul Kim; Ga Eun Kim; Yong Hyun Park; Soo Hyun Kim; Ji Youl Lee (Tissue Engineering and Regenerative Medicine, 2019)

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Development of a PCR test for detection of Xanthomonas campestris pv. raphani - Mehede Hassan Rubel; Mohammad Rashed Hossain; Ujjal Kumar Nath; Sathishkumar Natarajan; Ji-Hee Lee; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Australasian Plant Pathology, 2019)

Differential regional infarction, neuronal loss and gliosis in the gerbil cerebral hemisphere following 30 min of unilateral common carotid artery occlusion - Ji Hyeon Ahn; Minah Song; Hyunjung Kim; Tae-Kyeong Lee; Cheol Woo Park; Young Eun Park; Jae-Chul Lee; Jun Hwi Cho; Young-Myeong Kim; In Koo Hwang; Moo-Ho Won; Joon Ha Park (Metabolic Brain Disease, 2019)

Petrogenesis of Mesozoic granites at Garorim Bay, South Korea: evidence for an exotic block within the southwestern Gyeonggi massif? - Ji In Kim; Sung Hi Choi; Keewook Yi (Geosciences Journal, 2019)

Ascorbic Acid Attenuates Lead-Induced Alterations in the Synapses in the Developing Rat Cerebellum - Sung Min Nam; In-Sun Cho; Jin Seok Seo; Tae-Hun Go; Ji-Hye Kim; Sang-Soep Nahm; Byung-Joon Chang; Jong-Hwan Lee (Biological Trace Element Research, 2019)

Association of glutathione S-transferase M1 and T1 null/present polymorphism with physical performance in the Korean population - In Wook Hwang; Kicheol Kim; Bit Na Kwon; Hyung Jun Kim; Seung Hun Han; Noo Ri Lee; Eun Ji Choi; Hyun Ik Cho; Han Jun Jin (Genes & Genomics, 2019)

Hypoxia-Induced Neuroinflammation and Learning–Memory Impairments in Adult Zebrafish Are Suppressed by Glucosamine - Yunkyoung Lee; Sujeong Lee; Ji-Won Park; Ji-Sun Hwang; Sang-Min Kim; In Kyoon Lyoo; Chang-Joong Lee; Inn-Oc Han (Molecular Neurobiology, 2018)

Effects of CYP2C19 and CYP3A5 genetic polymorphisms on the pharmacokinetics of cilostazol and its active metabolites - Hye-In Lee; Ji-Young Byeon; Young-Hoon Kim; Choong-Min Lee; Chang-Ik Choi; Choon-Gon Jang; Jung-Woo Bae; Yun Jeong Lee; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2018)

Effects of CYP2D6 and CYP3A5 genetic polymorphisms on steady-state pharmacokinetics and hemodynamic effects of tamsulosin in humans - Kyoung-Ah Kim; In-Bae Park; Ji-Young Park (European Journal of Clinical Pharmacology, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Chemotactic effect of S100A8 and S100A9 on human eosinophilic leukemia cells, EoL-1 through TLR4 - Ayoung Gu; Da Hye Kim; Na Rae Lee; In Sik Kim; Ji-Sook Lee (Molecular & Cellular Toxicology, 2018)

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Real Data Assimilation Using the Local Ensemble Transform Kalman Filter (LETKF) System for a Global Non-hydrostatic NWP model on the Cubed-sphere - Seoleun Shin; Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Kwangjae Sung; Kyoungmi Cho; Youngsoon Jo; Jung-Eun Kim; In-Hyuk Kwon; Sujeong Lim; Ji-Sun Kang (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Multi-resolution Hybrid Data Assimilation Core on a Cubed-sphere Grid (HybDA) - Hyo-Jong Song; Ji-Hyun Ha; In-Hyuk Kwon; Junghan Kim; Jihye Kwun (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Potential silver nanoparticles migration from commercially available polymeric baby products into food simulants - Jeong In Choi; Song Ji Chae; Jung Min Kim; Jae Chun Choi; Se Jong Park; Hee Ju Choi; Hojae Bae; Hyun Jin Park (Food Additives & Contaminants: Part A, 2018)

Fisetin protects H9c2 cardiomyoblast cells against H2O2-induced apoptosis through Akt and ERK1/2 signaling pathways - Jeong Soo Lee; Ji-Sook Lee; Kyung Jae Cha; Dae-Eun Kim; Daye Lee; Sun Young Jung; Eun-Seok Park; In Sik Kim (Molecular & Cellular Toxicology, 2018)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions - In Kyung Kim; Sung-Woo Kim; A. M. Abd El-Aty; Md. Musfiqur Rahman; Md. Humayun Kabir; Han Sol Lee; Hyung Suk Chung; Ji Hoon Jeong; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Effects of vascular formation during alveolar bone process morphogenesis in mice - Seo-Young An; Ye-Ji Lee; Sanjiv Neupane; Jong-Hwa Jun; Ji-Youn Kim; Youngkyun Lee; Karp-Shik Choi; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Wern-Joo Sohn; Jae-Young Kim (Histochemistry and Cell Biology, 2017)

Plant growth promoting effect of Bacillus amyloliquefaciens H-2-5 on crop plants and influence on physiological changes in soybean under soil salinity - Min-Ji Kim; Ramalingam Radhakrishnan; Sang-Mo Kang; Young-Hyun You; Eun-Ju Jeong; Jong-Guk Kim; In-Jung Lee (Physiology and Molecular Biology of Plants, 2017)

Proteins derived from Prunus armeniaca kernel are possible to cause Immunoglobulin E reactivity in human sera - Kang-Hoon Kim; Ji Young Park; In-Seung Lee; Yumi Kim; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2017)

Chloroform induces cystein-rich 61, a mediator of collagen homeostasis via early growth response-1 dependent pathway in human skin dermal fibroblasts - Hana Lee; Jae Beom Park; Woo-In Ryu; Ji Hyun Kim; Jung Jin Shin; Sang Wook Son (Molecular & Cellular Toxicology, 2016)

Effect of house dust mite on neutrophil apoptosis by cytokine secretion in lymphocytes - Na Rae Lee; Ji-Sook Lee; Seung Yeop Baek; Da Hye Kim; Ayoung Gu; Seong Yeol Kim; Soo Jin Lee; In Sik Kim (Molecular & Cellular Toxicology, 2016)

Development and application of three-dimensional potential source contribution function (3D-PSCF) - In Sun Kim; Daehyun Wee; Yong Pyo Kim; Ji Yi Lee (Environmental Science and Pollution Research, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

Molecular characterization of the spike and ORF3 genes of porcine epidemic diarrhea virus in the Philippines - Yong Kwan Kim; Yoon-Young Cho; Byung-Hyun An; Seong-In Lim; Ji-Ae Lim; In-Soo Cho; Van Phan Le; Dong-Jun An (Archives of Virology, 2016)

Phentermine induces conditioned rewarding effects via activation of the PI3K/Akt signaling pathway in the nucleus accumbens - Sa-Ik Hong; Min-Jung Kim; In-Jee You; Seung-Hwan Kwon; Shi-Xun Ma; Ji-Young Hwang; Jee-Yeon Seo; Yong-Hyun Ko; Bo Ram Lee; Seok-Yong Lee; Choon-Gon Jang (Psychopharmacology, 2016)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

House dust mite allergen suppresses neutrophil apoptosis by cytokine release via PAR2 in normal and allergic lymphocytes - Na Rae Lee; Seung Yeop Baek; Ayoung Gu; Da Hye Kim; Seong Yeol Kim; Ji-Sook Lee; In Sik Kim (Immunologic Research, 2016)

Oncogenic role of SIRT1 associated with tumor invasion, lymph node metastasis, and poor disease-free survival in triple negative breast cancer - Soo Young Chung; Yoon Yang Jung; In Ae Park; Hyojin Kim; Yul Ri Chung; Ji Young Kim; Soo Young Park; Seock-Ah Im; Kyung-Hun Lee; Hyeong-Gon Moon; Dong-Young Noh; Wonshik Han; et al. (Clinical & Experimental Metastasis, 2016)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

LC-ESI-MS/MS analysis of phosphodiesterase-5 inhibitors and their analogues in foods and dietary supplements in Korea - Ji Hye Jeong; Ji Hyun Lee; Hyung Joo Kim; Hyoung Joon Park; In Sun Hwang; Kyoung Moon Han; Chang-Yong Yoon; Sooyeul Cho; Woo Seong Kim (Food Additives & Contaminants Part B-Surveillance, 2016)

Bladder reconstruction using stem cells seeded on multilayered scaffolds in a mucosa preserving partial cystectomy model - Kshitiz Raj Shrestha; Yong Hyun Park; Yong Sun Choi; In Gul Kim; Shuyu Piao; Ae Ryang Jung; Seung Hwan Jeon; Se Heang Oh; Jin Ho Lee; Ji Youl Lee (Tissue Engineering and Regenerative Medicine, 2015)

Serological surveillance studies confirm the Rift Valley fever virus free status in South Korea - Hyun Joo Kim; Jee-Yong Park; Hye-Young Jeoung; Jung-Yong Yeh; Yun-Sang Cho; Jeong-Soo Choi; Ji-Youn Lee; In-Soo Cho; Han-Sang Yoo (Tropical Animal Health and Production, 2015)

MicroRNA sequencing detects miR-424-5p up-regulation in ovarian cancer stem cells - Ji Ho Yun; Jisun Lim; In Su Ha; Ji Min Shin; Jung Hoon Kim; Jungho Kim; Chu Won Nho; Yoon Shin Cho (Genes & Genomics, 2015)

Erratum to: Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Erratum to: Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2015)

Inhibition effect of phenyl compounds from the Oryza sativa roots on melanin production in murine B16-F10 melanoma cells - Jin-Gyeong Cho; Jeongran Huh; Rak-Hun Jeong; Byeong-Ju Cha; Sabina Shrestha; Dong-Geol Lee; Hee-Cheol Kang; Ji-Young Kim; Nam-In Baek (Natural Product Research, 2015)

Coix seed extract attenuates the high-fat induced mouse obesity via PPARγ and C/EBPα a downregulation - Eun-Kyeong Choi; Yu Jeong Cho; Hea Jung Yang; Ki-Suk Kim; In-Seung Lee; Jong-Chan Jang; Kang-Hoon Kim; Ji Hyun Bang; Yumi Kim; Se Hoon Kim; Young-Hwan Cho; Na Young Yoon; et al. (Molecular & Cellular Toxicology, 2015)

Different anti-apoptotic effects of house dust mite allergen on eosinophil apoptosis between atopic and non-atopic asthmatic subjects - In Sik Kim; Mi Ae Im; Na Rae Lee; Seung Yeop Baek; Beom Seok Park; Ayoung Gu; Da Hye Kim; Ji-Sook Lee (Molecular & Cellular Toxicology, 2015)

A novel strain of porcine epidemic diarrhea virus in Vietnamese pigs - Yong Kwan Kim; Seong-In Lim; Ji-Ae Lim; In-Soo Cho; Eun-Hye Park; Van Phan Le; Nguyen Ba Hien; Pham Ngoc Thach; Do Hai Quynh; Tran Quang Vui; Nguyen Trung Tien; Dong-Jun An (Archives of Virology, 2015)

Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

MicroRNA expression profiling of p-phenylenediamine treatment in human keratinocyte cell line - Hwa Jun Cha; Ok-Kyu Lee; Soo Yeon Kim; Jung-Min Ko; Su Young Kim; Ji Hye Son; Hyun Joo Han; Shunhua Li; Soo Young Kim; Kyu Joong Ahn; In-Sook An; Sungkwan An; et al. (Molecular & Cellular Toxicology, 2015)

Characterization and miRNA-mediated posttranscriptional regulation of vitelline membrane outer layer protein I in the adult chicken oviduct - Sang In Lee; Mi-Ran Ji; Ye-Jin Jang; Mi-hyang Jeon; Jeom Sun Kim; Jin-Ki Park; Ik-Soo Jeon; Sung June Byun (In Vitro Cellular & Developmental Biology - Animal, 2015)

Polyphenols and antioxidant capacity of a spontaneous reddish mutant in Satsuma mandarin, Shinheungri - Min Young Kim; In-Jung Kim; Soon Jae Im; Ji Hye Kim; Ji-Man Heo; Seung-Yeob Song; Jung Hyun Kim; Seo Hyun Moon; Seongbeom Cho (Natural Product Research, 2014)

Simiduia aestuariiviva sp. nov., a gammaproteobacterium isolated from a tidal flat sediment - Sooyeon Park; Soo-In Kim; Chul-Hyung Kang; Ji-Min Park; Jung-Hoon Yoon (Antonie van Leeuwenhoek, 2014)

Developmental regulations of Perp in mice molar morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Girdhari Rijal; Ye-Ji Lee; Sanggyu Lee; Hitoshi Yamamoto; Chang-Hyeon An; Sung-Won Cho; Youngkyun Lee; Hong-In Shin; Tae-Yub Kwon; Jae-Young Kim (Cell and Tissue Research, 2014)

Anoctamin 1 expression in the mouse auditory brainstem - Sang Jae Cho; Ji Hyun Jeon; Do Ill Chun; Sang Won Yeo; In-Beom Kim (Cell and Tissue Research, 2014)

Evaluation of cloud and precipitation parameterization using a single-column model: A TWP-ICE case study - So-Young Kim; Ji-Young Han; In-Jin Choi; Soo Ya Bae (Asia-Pacific Journal of Atmospheric Sciences, 2014)

Dioscin induces caspase-independent apoptosis through activation of apoptosis-inducing factor in breast cancer cells - Eun-Ae Kim; Ji-Hoon Jang; Yun-Han Lee; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Suji Kim; Ho-Yong Sohn; Tae-Jin Lee (Apoptosis, 2014)

Halapricum salinum gen. nov., sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - Hye Seon Song; In-Tae Cha; Kyung June Yim; Hae-Won Lee; Dong-Wook Hyun; Sung-Jae Lee; Sung-Keun Rhee; Kil-Nam Kim; Daekyung Kim; Jong-Soon Choi; Myung-Ji Seo; Hak-Jong Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2014)

Halobellus rufus sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Myung-Ji Seo; Daekyung Kim; Jong-Soon Choi; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; et al. (Antonie van Leeuwenhoek, 2014)

Halorubrum halophilum sp. nov., an extremely halophilic archaeon isolated from a salt-fermented seafood - Kyung June Yim; In-Tae Cha; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Sung-Jae Lee; Young-Do Nam; Dong-Wook Hyun; Jin-Woo Bae; Sung-Keun Rhee; Myung-Ji Seo; Jong-Soon Choi; et al. (Antonie van Leeuwenhoek, 2014)

Global gene expression responses to waterlogging in leaves of rape seedlings - Yong-Hwa Lee; Kwang-Soo Kim; Young-Seok Jang; Ji-Hye Hwang; Dong-Hee Lee; In-Hu Choi (Plant Cell Reports, 2014)

Escitalopram block of hERG potassium channels - Yun Ju Chae; Ji Hyun Jeon; Hong Joon Lee; In-Beom Kim; Jin-Sung Choi; Ki-Wug Sung; Sang June Hahn (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Halococcus sediminicola sp. nov., an extremely halophilic archaeon isolated from a marine sediment - Kyung June Yim; In-Tae Cha; Tae Woong Whon; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Young-Do Nam; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; Jong-Soon Choi; Myung-Ji Seo; et al. (Antonie van Leeuwenhoek, 2014)

Phenolic components from Rhus parviflora fruits and their inhibitory effects on lipopolysaccharide-induced nitric oxide production in RAW 264.7 macrophages - Sabina Shrestha; Dae-Young Lee; Ji-Hae Park; Jin-Gyeong Cho; Dong-Sung Lee; Bin Li; Youn-Chul Kim; Geum-Soog Kim; Myun-Ho Bang; Nam-In Baek (Natural Product Research, 2013)

Comparative study on the fauna composition of intertidal invertebrates between natural and artificial substrata in the northeastern coast of Jeju Island - Jae-Hoon Cha; Kwang-Bae Kim; Ji-Na Song; In-Soo Kim; Jeong-Bin Seo; Chul-Hwi Kwoun (Ocean Science Journal, 2013)

Desulfotomaculum tongense sp. nov., a moderately thermophilic sulfate-reducing bacterium isolated from a hydrothermal vent sediment collected from the Tofua Arc in the Tonga Trench - In-Tae Cha; Seong Woon Roh; So-Jeong Kim; Hee-Ji Hong; Hae-Won Lee; Wan-Taek Lim; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

3-O-Acetyloleanolic acid exhibits anti-angiogenic effects and induces apoptosis in human umbilical vein endothelial cells - En-Ji Cui; Jeon Hwang-Bo; Jong-Hwa Park; Nam-In Baek; Jiyoung Kim; Seong Gil Hong; In Sik Chung (Biotechnology Letters, 2013)

Perverted Head Impulse Test in Cerebellar Ataxia - Seong-Hae Jeong; Ji-Soo Kim; In Chul Baek; Jong Wook Shin; Hyunjin Jo; Ae Young Lee; Jae-Moon Kim (The Cerebellum, 2013)

Different anti-apoptotic effects of normal and asthmatic serum on normal eosinophil apoptosis depending on house dust mite-specific IgE - In Sik Kim; Mi Jin Kim; Do Hyung Kim; Eugene Choi; Ji-Sook Lee (Molecular Biology Reports, 2013)

Nicastrin Overexpression in Transgenic Mice Induces Aberrant Behavior and APP Processing - Jun Seo Goo; Yong Bin Kim; Sun Bo Shim; Seung Wan Jee; Su Hae Lee; Ji Een Kim; In Sik Hwang; Young Ju Lee; Moon Hwa Kwak; Chuel Ju Lim; Jin Tae Hong; Dae Youn Hwang (Molecular Neurobiology, 2013)

The combined effects of transforming growth factor-β and basic fibroblast growth factor on the human degenerated nucleus pulposus cells in monolayer culture - Erxing He; Ji Hao Cui; Chuang Li; Cheng Tang; In-Sung Kim; Young-Woo Kim; Ho-Guen Chang; Jae-Ryong Cha; Oh-Jong Byung; Yong-Chan Kim (Tissue Engineering and Regenerative Medicine, 2013)

The relationship between antipsychotic D2 occupancy and change in frontal metabolism and working memory - Euitae Kim; Oliver D. Howes; Federico E. Turkheimer; Bo-Hyung Kim; Jae Min Jeong; Ji Who Kim; Jae Sung Lee; In-Jin Jang; Sang-Goo Shin; Shitij Kapur; Jun Soo Kwon (Psychopharmacology, 2013)

Erratum to: Regulation of arterial blood pressure by Akt1-dependent vascular relaxation - Jung Min Ha; Young Whan Kim; Dong Hyung Lee; Sung Ji Yun; Eun Kyoung Kim; In Hye Jin; Ji Hyun Kim; Chi Dae Kim; Hwa Kyoung Shin; Sun Sik Bae (Journal of Molecular Medicine, 2013)

Natural production of alkane by an easily harvested freshwater cyanobacterium, Phormidium autumnale KNUA026 - Jiwon Chang; Ji Won Hong; Hyunsik Chae; Han Soon Kim; Kyung Mok Park; Kyoung In Lee; Ho-Sung Yoon (Algae, 2013)

A (S)-(+)-decursin derivative, (S)-(+)-3-(3,4-dihydroxy-phenyl)-acrylic acid 2,2-dimethyl-8-oxo-3,4-dihydro-2H,8H-pyrano[3,2-g]-chromen-3-yl-ester, attenuates the development of atopic dermatitis-like lesions in NC/Nga mice - In Sik Kim; Dong-Hee Kim; Chi-Young Yun; Ji-Sook Lee (Molecular Biology Reports, 2013)

Comparative analysis of physicochemicals and antioxidative properties in new red rice (Oryza sativa L. cv. Gunganghongmi) - Woo Duck Seo; Jun Young Kim; You-Chun Song; Jun-Hyun Cho; Ki Chang Jang; Sang-Ik Han; Ji-Eun Ra; Seong-Hwan Oh; Hyeon-Jung Kang; Byung-Joo Kim; Nam-In Baek; Rak-Hun Jeong; et al. (Journal of Crop Science and Biotechnology, 2013)

Antisense-overexpression of the MsCOMT gene induces changes in lignin and total phenol contents in transgenic tobacco plants - Eun Soo Seong; Ji Hye Yoo; Jae Geun Lee; Hee Young Kim; In Seong Hwang; Kweon Heo; Jae Kwang Kim; Jung Dae Lim; Erik J. Sacks; Chang Yeon Yu (Molecular Biology Reports, 2013)

Prediction of the tacrolimus population pharmacokinetic parameters according to CYP3A5 genotype and clinical factors using NONMEM in adult kidney transplant recipients - Nayoung Han; Hwi-yeol Yun; Jin-yi Hong; In-Wha Kim; Eunhee Ji; Su Hyun Hong; Yon Su Kim; Jongwon Ha; Wan Gyoon Shin; Jung Mi Oh (European Journal of Clinical Pharmacology, 2013)

Synergistic Effect and Antibiofilm Activity Between the Antimicrobial Peptide Coprisin and Conventional Antibiotics Against Opportunistic Bacteria - In-sok Hwang; Jae-Sam Hwang; Ji Hong Hwang; Hyemin Choi; Eunjung Lee; Yangmee Kim; Dong Gun Lee (Current Microbiology, 2013)

Selenium Significantly Inhibits Adipocyte Hypertrophy and Abdominal Fat Accumulation in OLETF Rats via Induction of Fatty Acid β-Oxidation - Ji Eun Kim; Sun Il Choi; Hye Ryun Lee; In Sik Hwang; Young Ju Lee; Beum Soo An; Sang Hak Lee; Hak Jin Kim; Byeong Cheol Kang; Dae Youn Hwang (Biological Trace Element Research, 2012)

Chronological changes in inflammatory cytokines immunoreactivities in the mouse hippocampus after systemic administration of high dosage of tetanus toxin - Bing Chun Yan; Joon Ha Park; In Hye Kim; Bich Na Shin; Ji Hyeon Ahn; Ki-Yeon Yoo; Deuk-Sik Lee; Myong Jo Kim; Il-Jun Kang; Moo-Ho Won (Experimental Brain Research, 2012)

A missense mutation (c.1963A<G) of the complementary component 2 (C2) gene is associated with serum Ca++ concentrations in pigs - Jae-Bong Lee; Chae-Kyoung Yoo; Eun-Ji Jung; Jung-Hye Hwang; Bo-Young Seo; Byeong-Woo Kim; Hyun-Tae Lim; Jung-Gyu Lee; In-Cheol Cho; Hee-Bok Park (Molecular Biology Reports, 2012)

Hydroquinone-induced apoptosis of human lymphocytes through caspase 9/3 pathway - Ji-Sook Lee; Eun Ju Yang; In Sik Kim (Molecular Biology Reports, 2012)

Clinical and genetic factors affecting tacrolimus trough levels and drug-related outcomes in Korean kidney transplant recipients - In-Wha Kim; Yoo Jin Moon; Eunhee Ji; Kyung Im Kim; Nayoung Han; Sung Ju Kim; Wan Gyoon Shin; Jongwon Ha; Jeong-Hyun Yoon; Hye Suk Lee; Jung Mi Oh (European Journal of Clinical Pharmacology, 2012)

Determination of endocrine disrupting chemicals in water samples by dispersive liquid–liquid microextraction combined with liquid chromatography–fluorescence detection - Yeonsuk Ryu; Jung-In Lee; Jae-Won Moon; Jung-Hyun Kim; Ji-Hwan Park; Su-Yeon Park; Young A. Yoon; Jeongmi Lee (Journal of Pharmaceutical Investigation, 2012)

Gene expression analysis identifies DNA damage-related markers of benzo[a]pyrene exposure in HepG2 human hepatocytes - Mi-Kyung Song; Ji-Seong Yoon; Mee Song; Han-Seam Choi; Chan-Young Shin; Youn-Jung Kim; Woo-In Ryu; Hyo-Sun Lee; Jae-Chun Ryu (Toxicology and Environmental Health Sciences, 2012)

Cd2+ binds to Atx1 and affects the physical interaction between Atx1 and Ccc2 in Saccharomyces cerevisiae - Dong-Hyuk Heo; In-Joon Baek; Hyun-Jun Kang; Ji-Hyun Kim; Miwha Chang; Chang-Min Kang; Cheol-Won Yun (Biotechnology Letters, 2012)

Comparative analysis of expressed sequence tags (ESTs) between normal group and softness syndrome group in Halocynthia roretzi - Ji Eun Jeong; Se Won Kang; Yun Kyung Shin; Je Cheon Jun; Young-Ok Kim; Young Baek Hur; Jae-Hyung Kim; Sung-Hwa Chae; Jun-Sang Lee; In ho Choi; Yeon Soo Han; Dae-Hyun Seog; et al. (Molecular & Cellular Toxicology, 2011)

Regulation of arterial blood pressure by Akt1-dependent vascular relaxation - Jung Min Ha; Young Whan Kim; Dong Hyung Lee; Sung Ji Yun; Eun Kyoung Kim; In Hye Jin; Ji Hyun Kim; Chi Dae Kim; Hwa Kyoung Shin; Sun Sik Bae (Journal of Molecular Medicine, 2011)

Expression and immunohistochemical localization of TMEM16A/anoctamin 1, a calcium-activated chloride channel in the mouse cochlea - Ji Hyun Jeon; Jae Woo Park; Jong Woo Lee; Sung Won Jeong; Sang Won Yeo; In-Beom Kim (Cell and Tissue Research, 2011)

The effects of benzene and toluene on leukotactin-1-induced migration of EoL-1 cells - Bo Bae Song; Eun Ju Yang; Bo-Mi Kim; Ji-Sook Lee; Chi-Young Yun; Yang-Bin Im; In Sik Kim (Molecular & Cellular Toxicology, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Anti-angiogenic effects of the water extract of HangAmDan (WEHAD), a Korean traditional medicine - Ji-Young Bang; Kyung-Soon Kim; Eung-Yoon Kim; Hwa-Seung Yoo; Yeon-Weol Lee; Chong-Kwan Cho; YoungJin Choi; Hyun-Ja Jeong; In-Cheol Kang (Science China Life Sciences, 2011)

Correlation between nutrition intake and gene expression profiles in children with asthma - Jae-Eun Pie; Yu-Ri Kim; In-Kyoung Kim; Sang-Hui Seo; Seung Ho Lee; Hee Ra Lee; Young Yoo; Ji Tae Chung; Jong Pil Youn; MoonJu Oh; Seung Yong Hwang; Meyoung-Kon Kim (Molecular & Cellular Toxicology, 2010)

Effects of glyceollin I on vascular contraction in rat aorta - Min-Ji Song; Inji Baek; Su Bun Jeon; Minchul Seo; Yong-Hoon Kim; Song Cui; Yeon-Shin Jeong; In-Jung Lee; Dong Hyun Shin; Young Hyun Hwang; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Leukotactin-1/CCL15 induces cell migration and differentiation of human eosinophilic leukemia EoL-1 cells through PKCδ activation - Ji-Sook Lee; In Sik Kim (Molecular Biology Reports, 2010)

Arsenic detoxification potential of aox genes in arsenite-oxidizing bacteria isolated from natural and constructed wetlands in the Republic of Korea - Jin-Soo Chang; In-Ho Yoon; Ji-Hoon Lee; Ki-Rak Kim; Jeongyi An; Kyoung-Woong Kim (Environmental Geochemistry and Health, 2010)

Synaptic connections of calbindin-immunoreactive cone bipolar cells in the inner plexiform layer of rabbit retina - Shin Ae Kim; Choong Ki Jung; Tae-Hoon Kang; Ji Hyun Jeon; Jiook Cha; In-Beom Kim; Myung-Hoon Chun (Cell and Tissue Research, 2010)

AtObgC, a plant ortholog of bacterial Obg, is a chloroplast-targeting GTPase essential for early embryogenesis - Woo Young Bang; Akira Hata; In Sil Jeong; Tetsuya Umeda; Takayuki Masuda; Ji Chen; Ishizaki Yoko; I Nengah Suwastika; Dae Won Kim; Chak Han Im; Byung Hyun Lee; Yuno Lee; et al. (Plant Molecular Biology, 2009)

Doxycycline is Neuroprotective Against Nigral Dopaminergic Degeneration by a Dual Mechanism Involving MMP-3 - Yuri Cho; Hyo Jin Son; Eun-Mee Kim; Ji Hyun Choi; Sung Tae Kim; In Jung Ji; Dong Hee Choi; Tong H. Joh; Yoon Seong Kim; Onyou Hwang (Neurotoxicity Research, 2009)

Breeding of four-leaf white clover (Trifolium repens L.) through 60Co gamma-ray irradiation - In-Ja Song; Hong-Gyu Kang; Ji-Yeon Kang; Hae-Deun Kim; Tae-Woong Bae; Si-Young Kang; Pyung-Ok Lim; Taiji Adachi; Hyo-Yeon Lee (Plant Biotechnology Reports, 2009)

Assessment of Gene Flow from Genetically Modified Anthracnose-Resistant Chili Pepper (Capsicum annuum L.) to a Conventional Crop - Chang-Gi Kim; Dae In Kim; Hyo-Jeong Kim; Ji Eun Park; Bumkyu Lee; Kee Woong Park; Soon-Chun Jeong; Kyung Hwa Choi; Joo Hee An; Kang-Hyun Cho; Young Soon Kim; Hwan Mook Kim (Journal of Plant Biology, 2009)

Enhanced fungal resistance in Arabidopsis expressing wild rice PR-3 (OgChitIVa) encoding chitinase class IV - Jung-Hun Pak; Eun-Sook Chung; Sang-Hyun Shin; Eun-Hee Jeon; Mi-Jin Kim; Hye-Young Lee; Ji-Ung Jeung; Nam-In Hyung; Jai-Heon Lee; Young-Soo Chung (Plant Biotechnology Reports, 2009)

Arsenite oxidation by Alcaligenes sp. strain RS-19 isolated from arsenic-contaminated mines in the Republic of Korea - In-Ho Yoon; Jin-Soo Chang; Ji-Hoon Lee; Kyoung-Woong Kim (Environmental Geochemistry and Health, 2009)

Optimization of octanoic acid and sulfur donor concentrations for lipoic acid production by Pseudomonas reptilivora - Jung-Hwan Ji; In-Sik Yu; Hye-Jung Kim; Deok-Kun Oh (Biotechnology Letters, 2008)

Effects of ethanol extract from Saururus chinensis (Bour.) Baill on lipid and antioxidant metabolisms in rats fed a high-fat diet - Mi Hee Yu; Hyo Gwon Im; Ji-Won Lee; Mi-Hyang Hwang Bo; Hyun-Jeong Kim; Suk Kyung Kim; Shin Kyo Chung; In-Seon Lee (Natural Product Research, 2008)

Detection of gene flow from GM to non-GM watermelon in a field trial - Chang-Gi Kim; Bumkyu Lee; Dae In Kim; Ji Eun Park; Hyo-Jeong Kim; Kee Woong Park; Hoonbok Yi; Soon-Chun Jeong; Won Kee Yoon; Chee Hark Harn; Hwan Mook Kim (Journal of Plant Biology, 2008)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Vegetation of Barton Peninsula in the neighbourhood of King Sejong Station (King George Island, maritime Antarctic) - Ji Hee Kim; In-Young Ahn; Kyu Song Lee; Hosung Chung; Han-Gu Choi (Polar Biology, 2007)

ENA Actimineral Resource A restores bone loss and bone quality in ovariectomized rats - Sun Hee Do; Sung-Yong Hwa; Won-Il Jeong; Ji-Won Lee; Hyun-Jung Kim; In-Seon Lee; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Monitoring the occurrence of genetically modified soybean and maize around cultivated fields and at a grain receiving port in Korea - Chang-Gi Kim; Hoonbok Yi; Sangkyu Park; Ji Eun Yeon; Do Young Kim; Dae In Kim; Kyu-Hwa Lee; Taek Chang Lee; In Soon Paek; Won Kee Yoon; Soon-Chun Jeong; Hwan Mook Kim (Journal of Plant Biology, 2006)

Monitoring of petroleum hydrocarbon degradative potential of indigenous microorganisms in ozonated soil - Yeonghee Ahn; Haeryong Jung; Rameshwar Tatavarty; Heechul Choi; Ji-won Yang; In S. Kim (Biodegradation, 2005)

Numerical Phenetics of the Genus Spirogyra (Zygnematales, Chlorophyta) in Korea - Ji-Hwan Kim; Yeong-Hwan Kim; In-Gyu Lee (Algae, 2003)

Changes in gene expression during hairy root formation byAgrobacterium rhizogenes infection in ginseng - Hwa -Jee Chung; In Sook Cho; Jee -Hyub Kim; Dong Su In; Cheol Goo Hur; Ji Sook Song; Sung Sick Woo; Dong -Woog Choi; Jang Ryol Liu (Journal of Plant Biology, 2003)